A nationwide prospective cohort study on return to gainful occupation after stroke in Denmark 1996–2006. Issue 2 (17th October 2011) - Hannerz, Harald; Holbæk Pedersen, Betina; Poulsen, Otto M; Humle, Frank; Andersen, Lars L
Abstract : Background: Return to work is an important outcome factor for working-age patients poststroke. Previous epidemiological studies on this topic have been small (on average 125 patients per study). Their estimated effects are therefore associated with a tremendous statistical uncertainty. The present study estimates the effect of various predictors on the odds of returning to work after stroke in the total population of 20–57-year-old previously employed hospital treated patients with stroke in Denmark 1996–2006 (N=19 985). Methods and results: The patients were followed through national registers; 62% were gainfully occupied 2 years after stroke. The odds of returning to work were higher among people with intracerebral infarction, OR 1.0 (the reference group), than they were among people with subarachnoid haemorrhage, OR 0.79 (95% CI 0.71 to 0.88), and intracerebral haemorrhage, OR 0.39 (0.35 to 0.43). The odds of returning to work were lower among workers in elementary occupations OR 1.0 (reference group) than they were among workers in occupations that require skills at a basic level, OR 1.50 (1.38 to 1.64), technicians and associate professionals, OR 2.33 (2.05 to 2.65) and professionals, OR 3.04 (2.70 to 3.43). Patients in municipalities with a brain-injury rehabilitation centre did not have a better prognosis than patients in other municipalities, OR 0.91 (0.78 to 1.06). Being a woman, OR 0.79 (0.74 to 0.84), self-employed, OR 0.87 (0.78 to 0.96), or ≥50 years, OR 0.61 (0.57 to 0.65), was associated with an adverse prognosis. Conclusion: Further research is needed to explain the gender inequality, which suggests either a potential to improve return-to-work rates among the females or a tendency among the males to return too early.